Home-Ownership, Unemployed's Job Search Behavior and Post-Unemployment Outcomes - Marco Caliendo; Anne C. Gielen; Robert Mahlstedt (Institute for the Study of Labor (IZA), 2015)
Although home-ownership has been shown to restrict geographic labor mobility and to affect job search behavior of unemployed, there is no evidence so far on how it affects their future re-employment outcomes. We use two waves of detailed German survey data of newly unemployed individuals to study the effect of home-ownership on the job search behavior of unemployed and their re-employment outcomes. We show that unemployed who own a home are less willing to move and also less likely to apply for jobs for which one would have to move. However, we do not find any evidence for compensations of their restricted mobility by more intensive (more search channels or applications) or different (more active or informal) search behavior. Furthermore, we find that home-ownership does not seem to harm the employment prospects of the unemployed. Although the re-employment probability in the short-run is slightly lower, we find that after one year home-owning unemployed have found better re-employment jobs, in terms of wages and job satisfaction, than their renting counterparts.
Keywords: J64; J61; 330; job search behavior; home-ownership; search effort; reservation wage; unemployment duration